Activation of α‐Fe2O3 for Photoelectrochemical Water Splitting Strongly Enhanced by Low Temperature Annealing in Low Oxygen Containing Ambient. Issue 12 (11th February 2020) - Makimizu, Yoichi; Nguyen, Nhat Truong; Tucek, Jiri; Ahn, Hyo‐Jin; Yoo, JeongEun; Poornajar, Mahshid; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik
Abstract: Photoelectrochemical (PEC) water splitting is a promising method for the conversion of solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (α‐Fe2 O3 ) is one of the most attractive materials for a highly efficient charge carrier generation and collection due to its large specific surface area and the short minority carrier diffusion length. In the present work, the PEC water splitting performance of nanostructured α‐Fe2 O3 is investigated which was prepared by anodization followed by annealing in a low oxygen ambient (0.03 % O2 in Ar). It was found that low oxygen annealing can activate a significant PEC response of α‐Fe2 O3 even at a low temperature of 400 °C and provide an excellent PEC performance compared with classic air annealing. The photocurrent of the α‐Fe2 O3 annealed in the low oxygen at 1.5 V vs. RHE results as 0.5 mA cm −2, being 20 times higher than that of annealing in air. The obtained results show that the α‐Fe2 O3 annealed in low oxygen contains beneficial defects and promotes the transport of holes; it can be attributed to the improvement of conductivity due to the introduction of suitable oxygen vacancies in the α‐Fe2 O3 . Additionally, we demonstrate the photocurrent of α‐Fe2 O3 annealed in low oxygen ambient can be further enhanced by Zn‐Co LDH, which is a co‐catalyst of oxygen evolution reaction. This indicates low oxygen annealing generates a promising method to obtain an excellent PEC water splitting performance from α‐Fe2 O3 photoanodes. Abstract : Low oxygen annealing can activate a significant photoelectrochemical response of α‐Fe2 O3 even at a low temperature of 400 °C and provide an excellent PEC performance compared with classic air annealing. The α‐Fe2 O3 annealed in low oxygen ambient contains beneficial defects and promotes the transport of photogenerated holes; it can be attributed to the introduction of suitable oxygen vacancies in the α‐Fe2 O3 .